Efektivitas Penggunaan Aplikasi Kahoot sebagai Media Pembelajaran Game Based Learning pada Siswa Kelas VIII pada Mata Pelajaran Pendidikan Agama Islam di SMP Negeri 3 Padang Panjang - Aldino, Ahmad Raihan; Alfurqan, Alfurqan (Lembaga Yasin AlSys, 2025)
This study is motivated by low student engagement in the learning process and high levels of boredom resulting from the use of unengaging instructional media. The aim of this research is to examine the effectiveness of using the Kahoot application as a learning medium in Islamic Religious Education classes for Grade VIII students at SMP Negeri 3 Padang Panjang. A quantitative approach was employed using an experimental method with a pre-experimental design. Data collection techniques included pretest and posttest assessments, as well as questionnaires administered to 22 students selected through purposive sampling. The results indicate that the use of Kahoot has a positive impact on learning effectiveness. Hypothesis testing using the Product Moment Correlation Coefficient yielded an r value of 0.633, which exceeds the critical value of 0.444. Additionally, the t value of 4.01 surpasses the critical t value of 2.10 at a specified level of significance, indicating that the alternative hypothesis is accepted while the null hypothesis is rejected. These findings demonstrate that Kahoot is effective in enhancing students’ active participation and fostering a more interactive and enjoyable learning environment. The study concludes that Kahoot-based instructional media is appropriate for use in Islamic Religious Education classes to reduce boredom and actively increase student engagement.